1998
DOI: 10.1242/dev.125.16.3005
|View full text |Cite
|
Sign up to set email alerts
|

A signaling cascade involving endothelin-1, dHAND and Msx1 regulates development of neural-crest-derived branchial arch mesenchyme

Abstract: Numerous human syndromes are the result of abnormal cranial neural crest development. One group of such defects, referred to as CATCH-22 (cardiac defects, abnormal facies, thymic hypoplasia, cleft palate, hypocalcemia, associated with chromosome 22 microdeletion) syndrome, exhibit craniofacial and cardiac defects resulting from abnormal development of the third and fourth neural crest-derived branchial arches and branchial arch arteries. Mice harboring a null mutation of the endothelin-1 gene (Edn1), which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(2 citation statements)
references
References 55 publications
0
1
0
1
Order By: Relevance
“…По мере того как вентролатеральный поток проходит через передние половины сомитов, некоторые клетки остаются там и дифференцируются в дорсальные корешковые ганглии, в то время как другие дают начало симпатическим ганглиям [99], шванновским и адреномедуллярным клеткам [100,101]. Сердечный нервный гребень простирается от первого до третьего сомита и участвует в формировании сердечной перегородки, электрогенерирующей и проводящей системы сердца [102][103][104].…”
Section: -1879 ггunclassified
“…По мере того как вентролатеральный поток проходит через передние половины сомитов, некоторые клетки остаются там и дифференцируются в дорсальные корешковые ганглии, в то время как другие дают начало симпатическим ганглиям [99], шванновским и адреномедуллярным клеткам [100,101]. Сердечный нервный гребень простирается от первого до третьего сомита и участвует в формировании сердечной перегородки, электрогенерирующей и проводящей системы сердца [102][103][104].…”
Section: -1879 ггunclassified
“…The vertebrate jaw is characterized by dorso-ventral patterning in the rst pharyngeal arch via nested dlx expression and jagged-edn-bmp signaling (Talbot et al, 2010;Walker et al, 2006), producing an intermediate domain that expresses a suite of genes like gdf5 and nkx3.2 where the future jaw joint (Miller et al, 2003;Thomas et al, 1998). It has been shown that the transcription factor barx1 is involved with positioning this future jaw joint, as its expression is anti-correlated with this tissue, and its knockdown results in ectopic joint tissue in zebra sh (Nichols et al, 2013;Sperber & Dawid, 2008;Square et al, 2015).…”
Section: Introductionmentioning
confidence: 99%